Transient trimethylaminuria related to menstruation - Yamazaki Hiroshi; Cashman John R; Shimizu Makiko (BMC, 2007)
Abstract Background Trimethylaminuria, or fish odor syndrome, includes a transient or mild malodor caused by an excessive amount of malodorous trimethylamine as a result of body secretions. Herein, we describe data to support the proposal that menses can be an additional factor causing transient trimethylaminuria in self-reported subjects suffering from malodor and even in healthy women harboring functionally active flavin-containing monooxygenase 3 (FMO3). Methods FMO3 metabolic capacity (conversion of trimethylamine to trimethylamine N-oxide) was defined as the urinary ratio of trimethylamine N-oxide to total trimethylamine. Results Self-reported Case (A) that was homozygous for inactive Arg500stop FMO3, showed decreased metabolic capacity of FMO3 (i.e., ~10% the unaffected metabolic capacity) during 120 days of observation. For Case (B) that was homozygous for common [Glu158Lys; Glu308Gly] FMO3 polymorphisms, metabolic capacity of FMO3 was almost ~90%, except for a few days surrounding menstruation showing < 40% metabolic capacity. In comparison, three healthy control subjects that harbored heterozygous polymorphisms for [Glu158Lys; Glu308Gly] FMO3 or homozygous for wild FMO3 showed normal (> 90%) metabolic capacity, however, on days around menstruation the FMO3 metabolic capacity was decreased to ~60-70%. Conclusion Together, these results indicate that abnormal FMO3 capacity is caused by menstruation particularly in the presence, in homozygous form, of mild genetic variants such as [Glu158Lys; Glu308Gly] that cause a reduced FMO3 function.